2009
DOI: 10.1007/s10751-009-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of the TRIC experiment at COSY

Abstract: For the Time Reversal Invariance experiment at COSY (TRIC) that had been proposed at the Forschungszentrum Jülich a novel technique for measuring total cross sections in internal experiments was developed and the achievable precision of this measuring technique was tested. The experimental idea constitutes a true P-even T-odd null test of TRI. In order to compare to the theoretical upper bound from edm measurements (Haxton and Höring, Nucl Phys A560:469, 1993), the TRI violating observable A y,xz in proton-deu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The obvious disadvantage of this spin-filtering method is that, unless σ 1 /σ 0 is very large, the beam intensity would be much reduced before a significant polarization could be built up. There are some similarities here with the measurements of the beam lifetime discussed in connection with the TRIC experiment, the difference being that in the study of A y,y the beam was initially polarized [60].…”
Section: Spin-filtering Experimentssupporting
confidence: 64%
See 1 more Smart Citation
“…The obvious disadvantage of this spin-filtering method is that, unless σ 1 /σ 0 is very large, the beam intensity would be much reduced before a significant polarization could be built up. There are some similarities here with the measurements of the beam lifetime discussed in connection with the TRIC experiment, the difference being that in the study of A y,y the beam was initially polarized [60].…”
Section: Spin-filtering Experimentssupporting
confidence: 64%
“…The obvious disadvantage of this spin-filtering method is that, unless σ 1 /σ 0 is very large, the beam intensity would be much reduced before a significant polarization could be built up. There are some similarities here with the measurements of the beam lifetime discussed in connection with the TRIC experiment, the difference being that in the study of A y,y the beam was initially polarized [60]. A proof-of-principle experiment was carried out at the Test Storage Ring at Heidelberg using 23 MeV protons passing through a cell filled with transversally polarized hydrogen supplied by an atomic beam source.…”
Section: Spin-filtering Experimentsmentioning
confidence: 75%
“…A detailed discussion of the results obtained can be found in Ref. [11]. Three main conclusions were drawn:…”
Section: Feasibility Testmentioning
confidence: 79%
“…The effects of the breaking of time-reversal invariance can be searched for simultaneously in measurements of total cross sections using a beam-current transformer (BCT), and studies of differential observables using the PAX detection system. A status report about an earlier preparatory experiment carried out at COSY is given in [19]. The test beam time (Oct. 2006) has shown that the accuracy of the standard BCT is not sufficient to reach the necessary precision of 10 −6 in a timereversal non-invariance test.…”
Section: Time Reversal Invariance Test At Cosymentioning
confidence: 99%